A Critical Examination of Induction and African thought System (Global Journal of Human-Social Science, 2014)
Induction as a method of science is formulated from simple observation of particulars and their series, interconnectedness and order from whence general laws are derived. The highpoint of induction is centered on "particular instantiation" which informs the heart of the general conclusion. These being the case, one will wonder if this kind of culture or way of reasoning can be replicated in African thought system especially when it is common knowledge that the particular "individual" in African worldview is not seen nor heard but lost in the general scheme of things. How then can the individual be a basis for a general consensus about the truth of a matter? This inquiry informed the thrust of this work.
Keywords: induction; african; cosmology; thinking; logic; reality